Gender Identity: A Brief for Perinatal Nurses. Issue 5 (September 2018) - Wisner, Kirsten
Abstract : A growing number of individuals consider themselves gender nonbinary or gender nonconforming, defined as not identifying with a particular gender. This is especially true among our youth. It is important that clinicians understand related terminology and how to provide culturally competent care to this population. Our maternity nursing expert, Kirsten Wisner, offers insight on gender identity terminology and resources for appropriate care.